A new genotype of bovine leukemia virus in South America identified by NGS-based whole genome sequencing and molecular evolutionary genetic analysis. Issue 1 (December 2016) - Polat, Meripet; Takeshima, Shin-nosuke; Hosomichi, Kazuyoshi; Kim, Jiyun; Miyasaka, Taku; Yamada, Kazunori; Arainga, Mariluz; Murakami, Tomoyuki; Matsumoto, Yuki; Barra Diaz, Veronica; Panei, Carlos; González, Ester; et al.
Abstract Background Bovine leukemia virus (BLV) is a member ofretroviridae family, together with human T cell leukemia virus types 1 and 2 (HTLV-1 and -2) belonging to the genesdeltaretrovirus, and infects cattle worldwide. Previous studies have classified theenv sequences of BLV provirus from different geographic locations into eight genetic groups. To investigate the genetic variability of BLV in South America, we performed phylogenetic analyses of whole genome and partialenv gp51 sequences of BLV strains isolated from Peru, Paraguay and Bolivia, for which no the molecular characteristics of BLV have previously been published, and discovered a novel BLV genotype, genotype-9, in Bolivia. Results In Peru and Paraguay, 42.3 % (139/328) and over 50 % (76/139) of samples, respectively, were BLV positive. In Bolivia, the BLV infection rate was up to 30 % (156/507) at the individual level. In Argentina, 325/420 samples were BLV positive, with a BLV prevalence of 77.4 % at the individual level and up to 90.9 % at herd level. By contrast, relatively few BLV positive samples were detected in Chile, with a maximum of 29.1 % BLV infection at the individual level. We performed phylogenetic analyses using two different approaches, maximum likelihood (ML) tree and Bayesian inference, using 35 distinct partialenv gp51 sequences from BLV strains isolated from Peru, Paraguay, and Bolivia, and 74 known BLV strains, representing eight different BLV genotypes from various geographical locations worldwide. The results indicated that Peruvian and Paraguayan BLV strains were grouped into genotypes-1, -2, and -6, while those from Bolivia were clustered into genotypes-1, -2, and -6, and a new genotype, genotype-9. Interestingly, these results were confirmed using ML phylogenetic analysis of whole genome sequences obtained by next generation sequencing of 25 BLV strains, assigned to four different genotypes (genotypes-1, -2, -6, and -9) from Peru, Paraguay, and Bolivia. Comparative analyses of complete genome sequences clearly showed some specific substitutions, in both structural and non-structural BLV genes, distinguishing the novel genotype-9 from known genotypes. Conclusions Our results demonstrate widespread BLV infection in South American cattle and the existence of a new BLV genotype-9 in Bolivia. We conclude that at least seven BLV genotypes (genotypes-1, -2, -4, -5, -6, -7, and -9) are circulating in South America.